Analysis Of Mandibular Gonial Angle For Gender Determination - Alqaus, Muhamad Sahma; Apriyono, Dwi Kartika; Novita, Masniari; Supriyadi, Supriyadi; Prasetyarini, Swasthi (Poltekkes Kemenkes Semarang, 2025)
The gonial angle through radiomorphometry can be used in determining gender because it is the part of the mandible that experiences quite prominent and large transformative changes. Gender is an important parameter in identification. This study aims to determine whether there are differences in the size of the gonial angle through radiomorphometry in determining sex on panoramic radiographs aged â‰¥ 20 years. The method used analytical observational methods with a cross sectional approach and total sampling was 52 research samples (21 men and 31 women) gonial angle on panoramic radiography. The results showed that there was a significant difference in the size of the mandibular gonial angle between men and women. This study concludes that the gonial angle via radiomorphometry can be used to determine gender in panoramic radiography.